Mode II fracture toughness of glass–epoxy laminated composites under various heating conditions and strain rates. (2021) - Wei Xiang Ting, Eric; Chin Voon Sia, Charlie; Kannan Thangavelu, Saravana; Hing Chong, Kok; Joseph, Annie
Abstract: The high performance of glass fiber reinforced polymer (GFRP) leads this composite to become one of the favourite research topics in engineering. The GFRP is widely used in building structure and other engineering application. In the design of composite structures, the damage-tolerant consideration of composite structure is essential, especially under environmental factor and dynamic effect. Hence, the damage stability of the composite under loadings should be investigated. In this study, the mode II fracture toughness of glass/epoxy laminated composite is evaluated under various strain rates and heating temperatures. The GFRP laminated specimens were fabricated by hand layout method with the heat-treated temperature of 40 °C, 60 °C and 80 °C. The experimental mode II fracture toughness data were obtained from the end-notched flexure (ENF) test method with the strain rate from 1 mm/min to 5 min/min. The experimental results showed that the mode II fracture toughness of the GFRP laminate composite increase with the increase in strain rate. However, the mode II fracture toughness of the GFRP laminate composite is relatively insensitive to heating temperature..